2019
DOI: 10.34172/bi.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum induces apoptosis in gastric cancer cells via modulation of signaling pathways in Helicobacter pylori

Abstract: Introduction: Gastric cancer is considered the second prevalent cause of death around the world. This type of cancer is generally induced by Helicobacter pylori which could colonize within the gastric mucosa of the infected cases. To date, triple antibiotic therapy has routinely been utilized for controlling the H. pylori-induced infection. However, this strategy has been unsuccessful, in large part because of issues such as occurring point mutations in the H. pylori genome that can induce resistance to the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Lactobacillus shows anti-cancer activities. L. plantarum up-regulates the expression of PTEN , Bax , and TLR4 and down-regulates the AKT genes, and then promote the apoptosis of AGS cells[ 64 ]. In in vitro studies, L. gasseri causes a significant decrease in the expression of oncogenes including Bcl-2 , β-catenin, integrin α5, and integrin β1.…”
Section: Heterogeneous Effect Of Lactobacillus On Hostmentioning
confidence: 99%
“…Lactobacillus shows anti-cancer activities. L. plantarum up-regulates the expression of PTEN , Bax , and TLR4 and down-regulates the AKT genes, and then promote the apoptosis of AGS cells[ 64 ]. In in vitro studies, L. gasseri causes a significant decrease in the expression of oncogenes including Bcl-2 , β-catenin, integrin α5, and integrin β1.…”
Section: Heterogeneous Effect Of Lactobacillus On Hostmentioning
confidence: 99%
“…Recently, several in vitro and in vivo studies showed the protective effect of Lactobacillus on colorectal cancer, due to its anti‐inflammatory and anti‐proliferative properties 7,8 . Researches in the stomach discovered that Lactobacillus could inhibit growth and induce apoptosis in gastric cancer cells 9 . The administration of Lactobacillus is indicated to compete with H. pylori and mitigate H. pylori ‐induced gastritis in mice 10 .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Researches in the stomach discovered that Lactobacillus could inhibit growth and induce apoptosis in gastric cancer cells. 9 The administration of Lactobacillus is indicated to compete with H. pylori and mitigate H. pylori-induced gastritis in mice. 10 However, the impact of Lactobacillus on H. pylori-induced carcinogenesis remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“… 60 As shown in new report, Lactobacillus plantarum can inhibit both Helicobacter pylori colonization and a gastric cancer cell line (AGS) through the up-regulation of PTEN, BAX, TLR4, and the down-regulation of Akt genes. 30 Hence, blocking the hyperactivation of the PI3K/Akt/mTOR signaling pathway has emerged as a plausible therapeutic target for CRC and gastric cancers because of its involvement in cell growth and proliferation. However, the mechanisms of action involved in the beneficial effects of probiotics mediated through the PI3K/Akt/mTOR signaling pathway in GI disorders are not fully elucidated in relevant human models.…”
Section: Probiotics and Gastrointestinal (Gi) Disordersmentioning
confidence: 99%